The Changing “Weightscape” of Bulimia Nervosa - Bulik, Cynthia M. (2012)
Ms. Z, a 35-year-old African-American single woman with a body mass index (BMI) of 37.8 kg/m(2) (height 5 feet, 5.5 inches, weight 238 lb.), presents for an evaluation for bulimia nervosa. She was referred to the eating disorders program by her primary care physician who knew about her eating disorder, but was primarily concerned about her weight and blood pressure. Ms. Z has an advanced degree and is employed full time. She has struggled with her eating, weight, and body image since childhood and began binge eating regularly (1–2× week) at age 15. Fasting and self-induced vomiting began in her early twenties, when she achieved her lowest adult BMI of 21.6 kg (weight 130 lb. at age 23). She gained 100 pounds in the past 7 years and currently binges and purges 1–2 times a day. A typical binge consists of a box of cookies, a pint of ice cream, 7 oz. of cheese, two bowls of cereal with 2 cups of milk, and 4 pickles. Ms. Z has seen five therapists to address her eating behaviors and weight concerns and participated in numerous commercial weight loss programs. She states binge eating has always served a self-soothing purpose for her. Ms. Z has a demanding university-related job that absorbs most of her time. She has few friends and has not been in a romantic relationship for the past five years believing that no one would be interested in a woman of her size. She also claimed that food is more reliable than any man because “it’s always there when you need it and you don’t have to take care of it or stoke its ego.” She spends evenings at home working until she is completely exhausted, heads to the kitchen for an all-out binge, vomits everything up, and then cries herself to sleep. She has never smoked and does not drink alcohol. Current medications prescribed by her primary care physician include Fluoxetine (20 mg), Norvasc (5 mg), and Clonazepam (prn). What are Ms. Z’s treatment goals? What are her primary care physician’s? Is her medication for bulimia nervosa adequate? How well would cognitive-behavioral therapy for bulimia nervosa address her personal treatment goals? Her physician’s? What challenges might a therapist face having Ms. Z in group therapy for bulimia?